SOFT SKILLS DEVELOPMENT IN ACCOUNTING EDUCATION IN INDONESIA - Zoraifi, Renata (Prosiding Seminar Nasional Pendidikan Akuntansi dan Keuangan, 2015)
For many years universities around the world have placed studentsâ development of soft skills high on the agenda. However, limited empirical studies can be found on how these soft skills are perceived by stakeholders in accounting education in Indonesia. This paper reports some initial qualitative findings of professional literature on soft skills in Indonesia. There will be need for further research to study this academically as it will inform the accounting education reform in Indonesia.Â Keywords: Soft skills, Accounting education, Accounting education reform, Indonesia